Epizootiological and Epidemiological Situation on Leptospirosis in the Russian Federation over the Period of 2013–2022 and the Forecast for 2023 - D. V. Trankvilevsky; E. Yu. Kiseleva; V. M. Korzun; N. V. Breneva; Yu. A. Verzhutskaya; I. D. Zarva; O. N. Skudareva; S. V. Balakhonov (Проблемы особо опасных инфекций)
The aim of the work was to analyze the epizootic and epidemiological situation on leptospirosis in the territory of the Russian Federation in 2013–2022 and to forecast its development in 2023. The long-term dynamics of leptospirosis incidence in the Russian Federation tends to decrease. Cases were registered in 58 constituent entities of the Russian Federation, in all federal districts. The highest incidence rates were noted in the North-Western Federal District. When studying the material from small mammals using bacteriological, immunological and molecular-biological methods, Leptospira circulation was detected in 52 entities of the Russian Federation, in all federal districts. In 2023, sporadic cases of infection are to be expected in the territories of the North-Western Federal District, the Central Federal District, and the Southern Federal District; imported cases of infection from countries with subequatorial and equatorial climates are not excluded.